Leadership Ability Scale Among Female University Students (Journal of the College of Education for Women, 2019)
Find out the leadership ability among female university students.The researcher made aquestionnaire consisting ofone open question for (50) female students of education college for women\ Baghdad university to mention main leadership abilities with leader student.To achieve the aims of this study, the researcher made the following steps: 1- Collection and finalization the items of the scale Through literature review and previous studies and aquestionnaire consisting where (3) items have been extracted to make this questionnaire. 2- The test has been submitted to proffesionals of psychology to judge the valiidety of items of the scale where their opinion was they are good at (100%).The scale has been applied on statistical analysis sample consisting of (300) femal students of the 3rd and 4th grade in the following universities (Baghdad, Al- Mustansiriha, Al- Nharin) in Baghdad for the academic year (2015-2016). 4- Statistical analysis for the items (discrimination, validity of items).5- Some psychometric properties were conduced: The face validity. Reliability: Cronbach's alpha was used and the reliability score was (0,75). 6- After the results of statistical analysis for the scale and constancy and validity has been extracted, the researcher eliminated the where (3)items has been eliminated out of (30) items and kepton dicrimnative and statisticaly significant ones leading to the final scale consisting of (27) items. 7- The scale with its final form has been applied on (700) female students from the 3rd and 4th grade in the following universities (Baghdad, Al- Mustansiriha, Al- Nharin) in Baghdad for the academic year (2015-2016). 8- After the process of separation of answers, T-test has been applied on one sample, and the results showed that there were statisticaly signifigant differences at (0,05) level in the ability of femal students in leading where the calculated T- value was (117,35) which was larger than schudeled T- value which was (1,96) and the level of leadership ability among female university students was high. 9- The researcher concluded with anumber of suggestion and recommendations.